Fragmented QRS - A simple bedside non invasive predictor of early mortality and morbidity in STEMI - Abdul Mateen Athar; Zuber Suleman Kothi; Basanagouda S. Patil; Ashok P. Yenkanchi; Shruthi Kulkarni; Savitha Anne Sebastian (Al Ameen Medical College, 2016)
Background and objectives: Fragmented QRS encompasses different RSR' patterns showing various morphologies of the QRS complexes with or without the Q wave on a resting 12-lead electrocardiogram. It has been shown possibly to cause adverse cardiac outcomes in patients with some heart diseases, including coronary artery disease. In view of the need for risk stratification of patients presenting with acute coronary syndrome in the most efficacious and cost-effective way, we conducted this study to clarify the value of fragmented QRS in patients presenting with STEMI in predicting complication during hospital stay. Methods: Fifty consecutive patients admitted to the coronary care unit with their first STEMI were enrolled in this prospective observational study. Demographic and electrocardiographic data on admission, in hospital complication and mortality were recorded. Results: 50 patients were divided into two groups, one consisting of patients who developed fQRS (fQRS +ve) during hospital stay and the other group those who did not developed fQRS (fQRS -ve). Patients with fQRS on admission ECG had significantly higher incidence of arrhythmias (p=0.012), heart failure (p=0.008), hypotension (p=0.002) in comparison to patients with non fragmented QRS. In addition patients with more than one myocardial site involvement had higher incidence of fQRS (p=0.004). The mortality was significantly higher in fQRS positive (p= 0.029) group compared to fQRS negative group. Conclusion: This study strongly suggests that fragmented QRS on initial presentation with STEMI is predictive of subsequent events and provide very useful information in the risk stratification of acute STEMI patients.